The Effect of Meals Containing Culinary Doses of Spices on Postprandial Endothelial Function, Lipemia and Glycemia: A Randomized, Crossover, Controlled-Feeding Study. (14th June 2022) - Petersen, Kristina; Davis, Kristin; Proctor, David; Rogers, Connie; West, Sheila; Kris-Etherton, Penny
Abstract: Objectives: The objective was to examine the effect of meals containing 0.6 g (low-spice meal), 3.7 g (moderate-spice meal), and 7.4 g (high-spice meal) of herbs/spices on postprandial flow mediated dilation (FMD), triglycerides, insulin and glucose in men and post-menopausal women at-risk for cardiovascular disease. Methods: A 3-period, randomized, crossover, controlled-feeding study was conducted. Participants consumed an average American diet containing 0.5 (low-spice diet), 3.3 (moderate-spice diet), and 6.6 (high-spice diet) g/d/2100 kcal of herbs and spices for 4-weeks. At baseline and the end of each diet period, participants were given a meal challenge (1192 kcal; carbohydrate 145 g; protein 62 g; fat 44 g; saturated fat 20 g). The spice dose in the test meal corresponded to the spice level of the diet consumed for the previous 4 weeks. Blood was sampled at 0, 30, 60, 120, 180, 240 minutes for analysis of triglycerides, glucose, and insulin. FMD was measured at 0, 120 and 240 minutes. Results: The analytic sample included 43 participants (males 65%; age 48 ± 11 years; BMI 28.9 ± 2.9 kg/m 2, FMD 6.2 ± 2.3%). No between-meal differences were observed for FMD (meal P = 0.30; time P < 0.001; meal by time interaction P > 0.99). The area under the curve for triglycerides (P = 0.39), glucose (P = 0.49) and insulin (P = 0.07) was not different between the meals. Conclusions: Following intake of an average American diet with three different doses of spices (0.5, 3.3 and 6.6 g/d/2100 kcal) for 4-weeks, FMD, triglyceride, glucose and insulin responses to meals containing 0.6 g, 3.7 g and 7.4 g of spices were not different. These findings suggest that following 4-weeks of exposure to spice-containing diets, spice exposure from a meal does not dose-dependently affect endothelial function, lipemia and glucose homeostasis in the 4-hours post meal. Funding Sources: McCormick Science Institute; National Center for Advancing Translational Sciences, National Institutes of Health, through Grant UL1 TR002014.